Securing a claim in the economic and administrative process: a comparative legal aspect - Verbitska, Mariana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article is devoted to a comparative study of the features of securing a claim in administrative and commercial litigation.It is emphasized that the procedural institution of securing a claim is of great, and sometimes decisive, importance for the effective protection of the violated right of an individual or legal entity, that is, for the implementation of the fundamental principle of the rule of law, justice, one of the main elements of which is the real and final resolution of the case. After all, as determined by the Constitutional Court of Ukraine, justice in its essence is recognized as such only on the condition that it meets the requirements of justice and ensures effective restoration of rights.The author analyzes the specifics of measures to secure a claim in each of the specified processes, however, she also describes and examines the universal rules for submitting an application for securing a claim, requirements for such an application, etc. The article emphasizes different types of claim security in commercial and administrative proceedings, as well as the fact that the Code of administrative litigation of Ukraine does not provide for counter security.In the course of writing the publication, the author touches on the practical aspects of taking measures to secure a claim, analyzes judicial practice, in particular, the positions of the Supreme Court, in particular, both the Cassation Administrative Court and the Cassation Commercial Court.The result of conducting a study of the institute of securing a claim through the prism of comparison is the outline of certain problematic aspects related to the regulation of this procedural institute, as well as proposals for improving the legislative rules on this matter and, probably, universalizing practical approaches to issues related to securing a claim.In general, it has been established that securing a claim in the Ukrainian judiciary today works quite efficiently, is a common phenomenon, and is often applied.